The methodical approach to the study of the housing market of urban agglomerations of the “second-tier” - S. A. Kozhevnikov; N. V. Voroshilov; I. A. Kryukov (Модернизация, инновация, развитие)
Purpose: is to substantiate and test the methodological approach to the study of the housing market of “second-tier” urban agglomerations in a spatio-temporal projection.Methods: the methodological basis of the study was the theories of urban agglomeration and market integration. General scientific (analysis, synthesis, structural-functional), economic and statistical methods (identification of development trends, assessment of the integration of local housing markets), monographic analysis (research of approaches to market analysis), analysis of the regulatory framework were used.Results: the methodological approach to the study of the housing market of agglomerations is proposed and tested, the peculiarity of which is its analysis in a spatio-temporal projection based on analytics of Rosstat data and specialized information resources. Based on the results of its testing, the features of agglomerations were identified in terms of scale, spatial orientation of housing construction, and three types were identified: with an increase in the share of the core in the total volume of housing stock (Kaluga, Khanty-Mansiysk, Norilsk); core and one adjacent municipality (Vologda, Tambov, Yuzhno-Sakhalinsk); municipalities of the satellite zone (Arkhangelsk, Surgut). It is substantiated that the latter type is characteristic of agglomerations, that are generally at more mature stages of development. It was revealed that disproportions are manifested not only in the quantitative characteristics of housing, but its lower quality is noted in the satellite zone. It is shown that these features lead to a decrease in the potential for the development of integration processes in the market, which is also manifested in the weak transmission of price signals in the agglomeration space.Conclusions and Relevance: the hypothesis has been confirmed that in “second-tier” agglomerations, the agglomeration effects in the housing sector do not ensure spatial integration of the local core markets and satellite zone. It is substantiated that the movement towards integration is observed only in the Surgut and Arkhangelsk agglomerations. The results obtained can be used in the development of the strategic documents and projects for the development of these territories. The prospects of the study are seen in the development of institutional and economic foundations for the development of the housing market in agglomerations.